USAGE OF BAMBOO POWDER AS AN ADDITIVE IN ADOBE BRICKS AND BAMBOO CANES FRAME FOR THE REINFORCEMENT OF ADOBE STRUCTURE (2019)
The research shows the possibility to improve the resistance of adobe constructions using as a product, the processing waste, the bamboo powder. It can be used as additive in the mixture of the adobe bricks, increasing substantially their resistance. Those new bricks could be combined with an external reinforcement made by bamboo canes. Under normal operating conditions, the bamboo reinforcement does not collaborate with the adobe structure, but in case of strong exceptional events it is able to avoid the collapse of adobe walls. The tested solutions suit to solve many problems in crucial contexts in Latin America. In fact, this system can be built as self-construction, in environmental extremely precarious conditions, and it is also part of the traditional building knowledge of the populations to which it is addressed.